2015
DOI: 10.1007/s00436-015-4675-9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Hymenolepis spp. in pet rodents in Italy

Abstract: We carried out the first survey of Hymenolepis spp. infection in pet rodents in Italy. Fresh fecal samples were collected from 172 pet rodents as follows: guinea pigs (Cavia porcellus; n = 60), squirrels (Callosciurus finlaysonii, Callosciurus prevosti, Tamias striatus, Tamias sibiricus, Sciurus calorinensis; n = 52), hamsters (Phodopus campbelli, Mesocricetus auratus; n = 30), chinchillas (Chinchilla lanigera; n = 13), rats (Rattus norvegicus; n = 10), and mice (Mus minutoides; n = 7). These animals were hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Whether Callosciurus squirrels host zoonotic macroparasite needs further studies. In Italy, a case of two pet C. prevosti both infected with the cestode Hymenolepis diminuta, known also as rat tapeworm, was reported by d'Ovidio et al [143]. Only a few hundred cases of human infections by this species have been recorded, almost exclusively in children: although human hymenolepiasis is usually asymptomatic, sometimes severe symptoms occur (for details, see Reference [143]).…”
Section: Macroparasitesmentioning
confidence: 99%
“…Whether Callosciurus squirrels host zoonotic macroparasite needs further studies. In Italy, a case of two pet C. prevosti both infected with the cestode Hymenolepis diminuta, known also as rat tapeworm, was reported by d'Ovidio et al [143]. Only a few hundred cases of human infections by this species have been recorded, almost exclusively in children: although human hymenolepiasis is usually asymptomatic, sometimes severe symptoms occur (for details, see Reference [143]).…”
Section: Macroparasitesmentioning
confidence: 99%
“…This rate is considerably similar to that reported in the Belgrade area of Serbia (37%; Kataranovski et al, 2010) and the Tarai region of Uttarakhand (40–44%; Sharma et al, 2013). Conversely, it is higher than that reported in Korea (5%), the Philippines (19%; Fedorko, 1999), Grenada (16%; Coomansingh et al, 2009), Dhaka (27%; Gofur et al, 2010), Addis Ababa (7–27%; Gudissa et al, 2011), the Tabriz of Iran (4%; Garedaghi & Khaki, 2014), the suburban area of Hamadan City of Western Iran (17%; Yoisefi et al, 2014), Italy (29%; D'Ovidio et al, 2015), and the Heilongjiang Province of China (6–15%; Yang et al, 2017). It is also lower than the infection rate reported in Manila (64%; Tubangui, 1931), Japan (53%; Perec-Matysiak et al, 2006), Shiraz of Southern Iran (67%; Tanideh et al, 2010), the City of Aracaju in the Sergipe State of Brazil (67%; Guimarães et al, 2014), and Ahvaz of South-West Iran (63%; Rahdar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Waugh et al [14] reported on the zoonotic potential of helminths of R. rattus and Rattus norvegicus from Jamaica, recording the presence of six nematodes, two cestodes and an acanthocephalan. Fuehrer [15] reported the occurrence of Capillaria and Hymenolepis in wild rats in the United Kingdom, while d'Ovidio et al [16] and Garedaghi and Khaki [17] also reported on the presence of Hymenolepis diminuta in gray squirrel from Indiana and Hymenolepis species in captured rodents in Iran, respectively.…”
Section: Discussionmentioning
confidence: 99%